Electrical storm in the setting of amiodarone-induced long QT syndrome - Diaz Lazo, Anibal Valentin (2025)
A clinically significant case is reported, as it is the first to be published in the region. It refers to a patient who was admitted to the hospital through the emergency department after four days ofillness. The initial clinical presentation included lower limb edema and functional class II dyspnea, which progressed to class IV. A 12-lead electrocardiogram showed atrial tachycardia with a heart rate of 187 bpm. Sequential administration of adenosine, verapamil and electrical cardioversion was unsuccessful. Subsequently, amiodarone was given, leading to the restoration of sinus rhythm. On the second day of hospitalization, the patient developed frequent ventricular ectopic beats and episodes of supraventricular ectopic beats, for which amiodarone was continued. On the third day, he presented with an increased frequency of ventricular ectopy and non-sustained ventricular tachycardia, which progressed to sustained polymorphic ventricular tachycardia of the torsades de pointes type, accompanied by hemodynamic compromise, requiring multiple electrical shocks. The electrocardiogram after the shocks showed a prolonged QT interval. Management included discontinuation of amiodarone and correction of serum electrolyte disturbances such as hypokalemia and hypomagnesemia. Propranolol was administered, as isoproterenol is not available in our setting. Additionally, heart failure, renal dysfunction, and the infectious process were addressed. The patient had a favorable clinical course and was discharged 15 days after admission.